The Neonatal and Juvenile Pig in Pediatric Drug Discovery and Development - Miriam Ayuso; Laura Buyssens; Marina Stroe; Allan Valenzuela; Karel Allegaert; Anne Smits; Pieter Annaert; Antonius Mulder; Sebastien Carpentier; Chris Van Ginneken; Steven Van Cruchten (MDPI AG, 2020)
Pharmacotherapy in pediatric patients is challenging in view of the maturation of organ systems and processes that affect pharmacokinetics and pharmacodynamics. Especially for the youngest age groups and for pediatric-only indications, neonatal and juvenile animal models can be useful to assess drug safety and to better understand the mechanisms of diseases or conditions. In this respect, the use of neonatal and juvenile pigs in the field of pediatric drug discovery and development is promising, although still limited at this point. This review summarizes the comparative postnatal development of pigs and humans and discusses the advantages of the juvenile pig in view of developmental pharmacology, pediatric diseases, drug discovery and drug safety testing. Furthermore, limitations and unexplored aspects of this large animal model are covered. At this point in time, the potential of the neonatal and juvenile pig as nonclinical safety models for pediatric drug development is underexplored.